Denture cleaning — best practice. (2nd December 2019) - King, Elizabeth; Jagger, Robert
Abstract: Surveys have shown that many people do not clean their dentures effectively and suggest that the dental team may fail to educate patients in basic denture hygiene procedures. Poor denture hygiene can result in denture staining and malodour and is a risk factor for oral and systemic diseases. Methods available to clean dentures are described. Their modes of action, effectiveness and potential adverse effects are discussed. A combination of cleaning methods is probably more effective than any one method. Recommendations for effective denture cleaning that can be given to patients by the dental team are provided. CPD/Clinical Relevance: The dental team needs to explain effective approaches to denture hygiene to patients. Written information should also be provided to reinforce the message.